Haematogenous infection of a total knee arthroplasty with Klebsiella pneumoniae - Pepke, Wojciech; Lehner, Burkhard; Bekeredjian-Ding, Isabelle; Egermann, Marcus (BMJ case reports, 2013)
This case report describes a prosthetic joint infection due to the haematogenous spread of Klebsiella pneumoniae from a genitourinary focus. Prior to the infection, the patient was diagnosed with early stage prostatic carcinoma, which had been successfully treated with surgery. However, in the time period following surgical treatment, the patient suffered recurring urinary tract infections. During the course of these recurring infections, he developed a concurrent bacterial infection of his total knee arthroplasty. Two sequential joint aspirates revealed K pneumoniae to be the cause. Therefore, two-stage revision total knee arthroplasty was performed. This case reiterates the fact that invasive therapeutic procedures can cause bacteraemia resulting in infection of a joint replacement. We would therefore like to emphasise the importance of prophylactic antibiotic treatment prior to invasive therapies, particularly in organs with potentially large counts of bacteria.
Gesehen am 03.01.2022